2018
DOI: 10.22334/jbhost.v4i2.120
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work Environment Towards Turnover Intention of Employee of 4 Star Hotels in Padang City

Abstract: The purpose of this study was to analyze the influence of the work environment towards turnover intention of 4-star hotel employees in Padang City. This type of research is quantitative descriptive with a causal associative approach. The population in this study was 796 people consisting of all 4-star hotel employees in Padang City. The sample is 251 people using proportional random sampling technique. The data analysis technique used is simple linear regression analysis. The results of the study show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
1
2
0
6
Order By: Relevance
“…Berkaitan dengan hal tersebut, peneliti menemukan bahwa presentase turnover karyawan di Imelda Hotel Waterpark-Convention Padang berada diatas 10%. Angka turnover yang tinggi menunjukan bahwa manajemen kurang baik dalam mengelola karyawan, atau adanya keluhan-keluhan karyawan yang tidak ditanggapi serius oleh manajemen [4].…”
Section: Pendahuluanunclassified
“…Berkaitan dengan hal tersebut, peneliti menemukan bahwa presentase turnover karyawan di Imelda Hotel Waterpark-Convention Padang berada diatas 10%. Angka turnover yang tinggi menunjukan bahwa manajemen kurang baik dalam mengelola karyawan, atau adanya keluhan-keluhan karyawan yang tidak ditanggapi serius oleh manajemen [4].…”
Section: Pendahuluanunclassified
“…Work environment may have distinctive positive and negative impacts on employees' outcomes, for example, turnover intentions. Meirina, Ferdian, Pasaribu, and Suyuthie (2018) has demonstrated that work environment emphatically impacts on employee turnover intention of 4-star Hotels in Padang City with a relapse coefficient of 0.744, this suggests in case there is an extension within the estimation of the work environment by one unit it will make strides employee turnover by 0.744 units and vice versa. Arnoux-Nicolas, Sovet, Lhotellier, Di Fabio, and Bernaud (2016) has assessed that extended degrees of unfavourable working conditions would incite extended degrees of turnover intentions.…”
Section: Work Environment and Employee Turnovermentioning
confidence: 97%
“…Karyawan hotel bintang 5 sering mengalami stress karena pekerjaan yang banyak terutama pada departemen Fo, Hk,FBS,Fbp, dan Engginering. Tingkat hunian kamar tinggi akan menjadi beban oleh karyawan yang dapat menurunkan kinerja karyawan [2]. Smentara itu karyawan tetap dituntut untuk fokus dan maksimal, mengurangi kesalahan dalam bekerja, menjaga atau merawat peralatan hotel, tidak membuat perihal yang mengakibatkan keluhan dari tamu.…”
Section: Pendahuluanunclassified
“…Uraian sebelumnya merupakan penyebab stress. Jika tingkat stress tinggi akan menimbulkan keinginan untuk keluar dari pekerjaan [2], juga dapat menyebabkan terjadinya burnout. "Burnout yaitu keadaan stress secara psikologis yang sangat ekstrem sehingga individu mengalami kelelahan emosional dan motivasi yang rendah untuk bekerja.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation